A Content Analysis of Transformative Learning Theory - Edward W. Taylor; Patricia Cranton (Adult Education Research Conference, 2012)
For over a couple of years an edited handbook of transformative learning theory (TL), inclusive of an array of well-known scholars, has been under development (Taylor & Cranton, 2012). Its purpose is to provide a comprehensive and critical review of more than three decades of theory development, research, and practice in TL. In addition, it is an effort to promote the study of TL and prevent a reification of the theory, whereby its basic premises about learning have often become unquestioned in adult and higher education. The Handbook had four primary focuses: a) an historical/interdisciplinary development of the field, b) an analysis of the theory‘s greater sophistication in the development other conceptions of TL beyond the seminal work of Mezirow (1990, 2000); c) the practice of fostering TL with an emphasis on extra-rational ways of knowing; and d) discussion of areas for future research. Although this handbook will not be in publication until this summer it does offer an opportunity to explore the current issues facing the study of TL theory. Through an in-depth content analysis of over thirty chapters this paper explores what the chapters begin to reveal collectively about the study of TL theory. More specifically, it meant asking is there greater/lesser congruency among scholars about the nature of TL, its purpose, core elements, and essential practices? What new insights have been gained from bringing together these varying views of TL? And is there a better understanding of where the study of TL is headed in the next decade?